Sistem Prediksi Aturan Stock Obat Dengan Metode Iterative Dichotomiser (ID3) - Aida Fitriyani; Hiswara, Abrar; Fadila Fitria Rahmah (Journal of Informatic and Information Security, 2021)
Pharmacy has a lot of transaction data on the distribution of pharmaceutical supplies, especially drug management. There are several obstacles that occur in the drug supply management system at this pharmacy, one of which is the accumulation of drug stock, where pharmacists find it difficult to determine what drugs should be in stock or not in stock. In order to avoid the accumulation of drugs that exceed the user limit (expired) which will result in losses for pharmacies. For this reason, the authors want to deal with these problems through the Design of a web-based Drug Inventory Prediction Information System using the Itertive Dichotomiser Algorithm method which will predict the stock of drugs that are expected to manage drugs at pharmacies to be wiser in choosing products to sell. In designing information systems Supporting software is also used, namely PHP and MYSQL databases. The final result of this research is, with this information system, it can help pharmacists in supporting drug management so that they can be more selective in choosing the items to be purchased for sale so as to minimize losses that will occur in pharmacies.